2016
DOI: 10.1038/srep34108
|View full text |Cite
|
Sign up to set email alerts
|

Pre-fusion F is absent on the surface of formalin-inactivated respiratory syncytial virus

Abstract: The lack of a licensed vaccine for respiratory syncytial virus (RSV) can be partly attributed to regulatory hurdles resulting from vaccine enhanced respiratory disease (ERD) subsequent to natural RSV infection that was observed in clinical trials of formalin-inactivated RSV (FI-RSV) in antigen-naïve infants. To develop an effective vaccine that does not enhance RSV illness, it is important to understand how formalin and heat inactivation affected the antigenicity and immunogenicity of FI-RSV compared to native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 26 publications
(32 reference statements)
6
82
0
2
Order By: Relevance
“…However, results from a sandwich enzyme-linked immunosorbent assay (ELISA) showed that the binding of 5C4 to virions was significantly lower than that of 1129 (Fig. 1F), indicating that the F on virions is unstable and spontaneously flips from the pre-F into the post-F conformation, which is consistent with prior reports (5,11).…”
Section: Importancesupporting
confidence: 89%
“…However, results from a sandwich enzyme-linked immunosorbent assay (ELISA) showed that the binding of 5C4 to virions was significantly lower than that of 1129 (Fig. 1F), indicating that the F on virions is unstable and spontaneously flips from the pre-F into the post-F conformation, which is consistent with prior reports (5,11).…”
Section: Importancesupporting
confidence: 89%
“…In addition, our results show that a relatively large fraction of the infant antibody response is directed against antigenic site I, which is well-exposed on postF. Antibodies targeting this site generally lacked neutralizing activity, suggesting that vaccination with postF antigens could drive infant antibody responses toward ineffective recognition of RSV F. Formalin-inactivated RSV (FI-RSV), the preparation that resulted in vaccine-enhanced disease in infants in the 1960s, displays an abundance of postF on the surface of the virus (Killikelly et al, 2016). Although many factors contribute to the development of vaccine-enhanced disease (Acosta et al, 2015), our data suggest that the high abundance of postF on FI-RSV could result in the induction of high levels of site I-directed antibodies and a low fraction of neutralizing antibodies, which is a property associated with the formation of immune complexes that contribute to lung pathology in vaccine-enhanced illness (Murphy and Walsh, 1988; Polack et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The fusion peptides, located at the amino termini of the F 1 subunits, are buried inside the central cavity of the protein. This prefusion conformation of F is unstable and has a low energy barrier to refolding, as evidenced by the accumulation of the refolded postfusion form of the protein on the surface of virions as a function of time 77,78 . During the refolding process, the fusion peptides are withdrawn from the central cavity and are projected away from the viral membrane, as secondary structure elements in the F 1 subunits refold into a long α-helix (FIg.…”
Section: Fusion Glycoproteinmentioning
confidence: 99%
“…After budding from the apical membrane of polarized epithelial cells, virions detach and are released in a m-dependent maturation process as filamentous particles ~130 nm in diameter and 0.5-12 micrometres in length 170,173,174 . over time, the m layer dissociates from the viral membrane, creating non-filamentous regions in the virion that ultimately lead to spherical or pleiomorphic particles that are thought to be less infectious, likely owing to a premature conversion of the F protein from the prefusion to postfusion conformation 77,78 . HSPG, heparan sulfate proteoglycan.…”
Section: Box 1 | the Life Cycle Of Respiratory Syncytial Virusmentioning
confidence: 99%